Distance learner's satisfaction towards information technology usage - Abu Mansor, Nur Naha; Ismail, Maimunah (Universiti Putra Malaysia Press, 2001)
The study focuses on learner's satisfaction towards Information Technology (IT) usage in Distance Education (DE) programmes. The first objective is to determine the satisfaction level of learners towards Internet and Website usage in terms of facilities, presentation mode and support services provided. Secondly, it determines the difference in learners' satisfaction level towards Internet and Website usage with learner backgrounds in the various aspects of ethnicity, gender, type of organization, type of profession, computer experience and educational achievement. Data were from 81 distance learners of UPM, collected using self-administered questionnaires. Results showed that respondents' satisfaction level On the overall usage of IT in their learning was of model-ate satisfaction. There "''as no difference in learners' satisfaction level of IT usage towards the aspects of facilities, presentation mode and support services provided with learners' background of ethnicity, gender, type of employer, type of profession, computer experience, and educational attainment. The study suggests some recommendations in order to improve the current practice of Distance Education using IT.